PENGARUH ARUS KAS, RETURN ON INVESTMENT, MANAJEMEN LABA DAN DIVIDEND POLICY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Windana, Salistiya; Syahputri, Marlina; Pakpahan, Desty Seria; Ginting, Bobby; Dini, Siti (EDUTECH CONSULTANT, 2019)
The research approach used is quantitative and the type of research is descriptive. The population used is the Food and Beverage Company listed on the Indonesia Stock Exchange in 2012-2017. The sample selection uses a purposive sampling method. The collected data is analyzed first by testing the classical assumptions before testing the hypothesis. Testing the hypothesis used is multiple linear regression analysis, t test, F test and coefficient of determination. The results show that partially Cash Flow has a positive and significant effect on Firm Value, while Return On Investment, Earnings Management and Dividend Policy have a negative and not significant effect on Firm Value. Simultaneously Cash Flow, Return On Investment, Profit Management and Dividend Policy have a positive and significant effect on Firm Value.